PEMBENTUKAN KARAKTER SISWA MELALUI PEMBELAJARAN UNJUK KERJA KARYA DI SDN BANYU URIP III SURABAYA - Afina Syabila Rahma (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2024)
This study aims to analyze work performance learning that influences the formation or development of student character. The research method used is a qualitative method with data collection techniques through observation and interviews. Data analysis in this research includes data reduction and drawing conclusions. The results of this study indicate that the learning performance of this work is very important for the formation of student character, in this case the teacher also plays a very important role in the formation of student character. The teacher does not only act as a teacher, but also as a role model for students.